The Usability Measurement of E–Faculty of Education UNESA Service Using USE Questionnaire - Haq, Mohammad Syahidul; Wagino, Wagino; Rofiah, Khofidotur; Setyowati, Nur Aini Dwi (Universitas Negeri Malang, 2021)
In this 21st-century era, the development of a management information system is one of the efforts that can be made to improve the quality of public services, both in general and in certain sectors, for example, education, where because of the effect of industrial revolution 4.0 and society 5.0, these days the community often to use the assistance of technology for their social activities. One of many ways that can be used to measure the success rate of a system is using usability measurement. The usability level of an information system shows whether the system is accepted by the user or not. This study aims to measure the usability level of the educational service in the Faculty of Education, State University of Surabaya (UNESA), using the USE Questionnaire. The data from this research are processed using a descriptive statistics method and then analyzed both for each aspect and the correlation of all aspects. The results of this study included; (1) the usefulness aspect got an eligibility percentage of 83,6%; (2) the ease of use aspect got an eligibility percentage of 81,7%; (3) the satisfaction aspect got eligibility percentage of 79,8%; (4) the result of calculation of all usability aspects are 81,9%, meaning that the E-Service Faculty of Education, Unisa very useful and worthy to be used.